The Use of Scrapbook Media in Mathematics Learning for Elementary School Students - Sarah Marwa Nabila; Berta Apriza; Karsoni Berta Dinata (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Mathematics is a basic science that not only teaches numbers and calculations but also trains logical, analytical, systematic, and critical thinking skills in solving contextual problems related to everyday life. This study examines the effectiveness of using scrapbook media in mathematics learning in elementary schools through the Systematic Literature Review (SLR) method. The literature search focused on the first keyword, "Scrapbook", resulting in 105,000 articles, then limited to 2020 to 2024 with 13,700 articles. The insertion of the second keyword, "Mathematics Learning", obtained 380 articles, and then the placement of the third keyword "Elementary School", obtained 332 articles. Data filtering is also required from the 332 articles, and a feasibility test is still carried out, thus obtaining articles that align with the focus of the literature review objectives. The review process was done through the identification, selection, and feasibility stages based on inclusion and exclusion criteria. Of the 332 articles found, only 10 met the in-depth analysis requirements. The study results show that scrapbooks can help students understand mathematical concepts visually, concretely, and enjoyably. Furthermore, scrapbooks have been shown to increase student interest in learning, creativity, and active engagement during the learning process. Scrapbooks also support contextual learning and strengthen the connection between mathematical concepts and real-life situations. Based on these findings, scrapbooks are recommended as a practical and relevant alternative medium for improving the quality of mathematics learning in elementary schools.